2017
DOI: 10.1089/rej.2016.1912
|View full text |Cite
|
Sign up to set email alerts
|

Tanshinone IIA Elicits Neuroprotective Effect Through Activating the Nuclear Factor Erythroid 2-Related Factor-Dependent Antioxidant Response

Abstract: Tanshinone IIA (TSA), a principal component derived from the Traditional Chinese Medicine Danshen has been suggested to exert neuroprotective effect against experimental cerebral ischemic/reperfusion injury. But the associated underlying mechanisms still have not been understood. The current study characterized the role of nuclear factor erythroid two-related factor-induced antioxidant response in the neuroprotective efficacy of TSA treatment. The focal cerebral ischemia/reperfusion model was established by 60… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
33
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(35 citation statements)
references
References 34 publications
2
33
0
Order By: Relevance
“…In this study, Tanshinone IIA preconditioned rats with CIN exhibited lower levels of oxidative stress. The results were consistent with previous studies which focused on Tanshinone IIA for neurologic injury [15]. In the present study, we demonstrated that Tanshinone IIA has protective effects on CIN, and that these protective effects are related, at least in part, to its anti-oxidative properties.…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…In this study, Tanshinone IIA preconditioned rats with CIN exhibited lower levels of oxidative stress. The results were consistent with previous studies which focused on Tanshinone IIA for neurologic injury [15]. In the present study, we demonstrated that Tanshinone IIA has protective effects on CIN, and that these protective effects are related, at least in part, to its anti-oxidative properties.…”
Section: Discussionsupporting
confidence: 94%
“…A recent study reported that Tanshinone IIA could up-regulate the expression of Bcl-2, an anti-apoptotic protein [10]. On another hand, it was also reported Nrf2 activation contributed to Tanshinone IIA induced neuroprotection by inducing transcription of large numbers of antioxidant genes including heme oxygenase-1 (HO-1) [15]. We hypothesized that Tanshinone IIA might play the same role in preventing CIN.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have reported that Tan IIA exhibits antioxidant, anti-inflammatory, and anticancer activities via multiple effects. In acute stress, Tan IIA alleviates the ischemia-reperfusion injury of the heart [ 7 ], liver [ 8 ], brain [ 9 ] and kidneys [ 10 ]. In chronic metabolic disorder, Tan IIA inhibits adipogenic differentiation [ 11 ], fatty liver disease [ 8 ] and diabetic cardiomyopathy [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Protective effects were also partly mediated by its anti-inflammatory effect on macrophage migration inhibition factor (MIF) expression, NF-κB activity, the release of proinflammatory cytokines (TNF-α and IL-6), and the reduction of neutrophil infiltration together with antiapoptotic effects by the reduction of caspase-3 expression and increased B-cell lymphoma 2 (bcl-2) protein expression in the ischemic cortex [92]. Nrf2 activation by tanshinone IIA treatment increased the content of antioxidant enzymes and reduced the generation of oxidative products after focal brain ischemia [96]. All these findings suggest great potential of tanshinone IIA in ischemic brain damage.…”
Section: Tanshinonesmentioning
confidence: 99%